2017
DOI: 10.1186/s12864-017-3881-5
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite marker development by partial sequencing of the sour passion fruit genome (Passiflora edulis Sims)

Abstract: BackgroundThe Passiflora genus comprises hundreds of wild and cultivated species of passion fruit used for food, industrial, ornamental and medicinal purposes. Efforts to develop genomic tools for genetic analysis of P. edulis, the most important commercial Passiflora species, are still incipient. In spite of many recognized applications of microsatellite markers in genetics and breeding, their availability for passion fruit research remains restricted. Microsatellite markers in P. edulis are usually limited i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 61 publications
1
32
0
3
Order By: Relevance
“…The SSR Search software [16] and homologous annotation were used to annotate the repeated sequences in passion fruit genome. The results showed that there were 428,294 full-type SSR and 1,544,549 incomplete- and composite-type SSR [6]. For transposons, there were 59 Mutator transposons, 41 EnSpm transposons, 49 hAT transposons, 221 PIF transposons, and 2 MLE transposons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSR Search software [16] and homologous annotation were used to annotate the repeated sequences in passion fruit genome. The results showed that there were 428,294 full-type SSR and 1,544,549 incomplete- and composite-type SSR [6]. For transposons, there were 59 Mutator transposons, 41 EnSpm transposons, 49 hAT transposons, 221 PIF transposons, and 2 MLE transposons.…”
Section: Resultsmentioning
confidence: 99%
“…Santos et al [5] used BAC end sequencing method to obtain 6,194,248 bp of passion fruit genome data, in which 669 microsatellite sequences were found, with an average of one SSR per 9.25 kb genome sequence. Later, Araya et al [6] developed 816 pairs of SSR primers in the structural and functional regions using parts of the passion fruit genome sequence. The results showed that 53.2% of SSR primers were polymorphic.…”
Section: Introductionmentioning
confidence: 99%
“…A taxa de transferibilidade variou de 14,28 a 33,33%, estudos anteriores relataram essa variação na taxa de transferibilidade de primers SSR em Passifloraceae (Oliveira et al, 2013;Paiva et al, 2014b;Pereira et al, 2015;Araya et al, 2017).…”
Section: Resultsunclassified
“…Estudos como este que avaliam a transferibilidade de primers microssatélites em Passifloracea tornam-se extremamente úteis, pois são ferramentas que antecedem estudos na área da genética vegetal, possibilitando medir os efeitos evolutivos e de seleção natural das espécies, e realizar análises filogenéticas, construções de mapas gênicos, análise de diversidade genética, e estudos de preservação da população durante programas de melhoramento genético (Gonçalves-Vidigal & Rubiano, 2011;Pereira et al, 2015). Além de serem capazes de acompanhar relações intra e interespécies (Araya et al, 2017), e serem utilizados na confirmação de paternidade de híbridos (Belo et al, 2018), otimizando assim os estudos de caracterização molecular das espécies silvestres de maracujazeiro, uma vez que através da análise de transferibilidade é possível otimizar os custos onerosos e longos períodos de desenvolvimento de novos marcadores SSR.…”
Section: Resultsunclassified
See 1 more Smart Citation